Varied behavioral responses induced by morphine in the tree shrew: a possible model for human opiate addiction - Shen, Fang; Duan, Ying; Jin, Shubo; Sui, Nan (Frontiers in Behavioral Neuroscience, 2014)
Tree shrews represent a suitable animal model to study the pathogenesis of human diseases as they are phylogenetically close to primates and have a well-developed central nervous system that possesses many homologies with primates. Therefore, in our study, we investigated whether tree shrews can be used to explore the addictive behaviors induced by morphine. Firstly, to investigate the psychoactive effect of morphine on tree shrews’ behavior, the number of jumping and shuttling, which represent the vertical and horizontal locomotor activity respectively, was examined following the injection of different dosage of morphine. Our results showed intramuscular (IM) injection of morphine (5 or 10 mg/kg) significantly increased the locomotor activity of tree shrews 30-60 min post-injection. Then, using the conditioned place preference/aversion (CPP/CPA) paradigm, we found morphine-conditioned tree shrews exhibited place preference in the morphine-paired chamber on the test day. In addition, naloxone-precipitated withdrawal induced place aversion in the chronic morphine-dependent tree shrews. We evaluated the craving for morphine drinking by assessing the break point that reflects the maximum effort animals will expend to get the drug. Our data showed the break point was significantly increased when compared to the baseline on the 1st, 7th and 14th day after the abstinence. Moreover, in the intravenous morphine self-administration experiment, tree shrews conditioned with morphine responded on the active lever significantly more frequently than on the inactive lever after training. These results suggest that tree shrew may be a potential candidate for study the addictive behaviors and the underling neurological mechanisms.